Pre-exercise carbohydrate status and immune responses to prolonged cycling: I. Effect on neutrophil degranulation - Bishop, N. C.; Walsh, N. P.; Haines, D. L.; Richards, E. E.; Gleeson, M. (International Journal of Sport Nutrition and Exercise Metabolism, 2001)
Ingesting carbohydrate (CHO) beverages during heavy exercise is associated with smaller shifts in numbers of circulating neutrophils and attenuated changes in neutrophil functional responses. The influence of dietary CHO availability on these responses has not been determined. Therefore, the present study investigated the influence of pre-exercise CHO status on circulating neutrophil and lipopolysaccharide (LPS)-stimulated neutrophil degranulation responses to prolonged cycling. Twelve trained male cyclists performed a glycogen-lowering bout of cycling and were randomly assigned to follow a diet ensuring either greater than 70% (HIGH) or less than 10% (LOW) of daily energy intake from CHO for the next 3 days. On day 4, subjects performed an exercise test that comprised cycling for 1 hour at 60% Wmax immediately followed by a time-trial (TT) ensuring an energy expenditure equivalent to cycling for 30 min at 80% Wmax. Subjects repeated the protocol after 7 days, this time following the second diet. The order of the trials was counterbalanced. At TT completion, the HIGH compared with the LOW trial was associated with higher plasma glucose concentration, lower plasma cortisol concentration, and lower circulating neutrophil count. LPS-stimulated neutrophil degranulation per cell fell similarly on both trials. These findings suggest that pre-exercise CHO status influences neutrophil trafficking but not function in response to prolonged cycling.